PENGARUH MEDIA INTERAKTIF WORDWALL TERHADAP KEMAMPUAN MEMBACA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ASSYOFA PADANG - Humayro; Serli Marlina; Yulsyofriend; Rismareni Pransiska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to find out the effect of the interactive Wordwall media on the reading skills of 5–6-year-old children at TK Assyofa Padang. The research uses a quantitative approach with a quasi-experimental method, involving 30 children as samples divided into an experimental class and a control class. Data collection was done using a checklist test with 5 statements, while data analysis was carried out through normality test, homogeneity test, and independent sample t-test using SPSS 25. The results show a sig (2-tailed) value of 0.036 < 0.05, which means Ha is accepted, with an average increase in reading skills in the experimental class (18.53) being higher than in the control class (17.53). Therefore, it can be concluded that the interactive Wordwall media has a significant effect on improving early childhood reading skills and can be used as an innovative learning media alternative.